Islamic Character Camp: Establishing Students Altruism Intelligence with Da’wa Communication - Yuliana Rakhmawati (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2020)
Altruism is one part of the Islamic teachings to hone people’s care of others. Altruism da’wa in Islam as a form of teachings or principles should be taught to people from an early age or childhood. Altruistic character building can be started from the primary education environment. The purpose of this research was to describe the urgency and function of establishing the altruism character in the Ulil Albab Integrated Islamic Elementary School (SDIT) through the Islamic Character Camp. This research was conducted using a qualitative approach. Meanwhile, a theoretical sampling obtained the SDIT’s principal and ICC’s person in chief for interviews. The results showed that SDIT Ulil Albab held da’wa communication by repackaging altruism messages and methods adjusted to the target, namely elementary school students. Strengthening the messages of altruism on an ongoing basis with alternative and contemporary media is necessary for future research.